On the methods of appointing (determining) tax collectors - Majka, Paweł; Brzezicki, Tomasz; Wantoch-Rekowski, Jacek (Studia Iuridica Toruniensia, 2025)
The subject of the study is the analysis of legal regulations regarding the appointment of a collector of local taxes and fees. The aim of the study is to determine whether the definition of a tax collector in a resolution of the Commune Council should be made by indicating individual data, i.e., his name and surname or name in relation to organizational units, or whether it is sufficient to indicate his generic characteristics, for example, by specifying a function performed or running specific activities. In the authors’ opinion, the second concept is correct. At the same time, the presented analysis showed that the practice of appointing tax collectors over several decades has not developed a uniform practice. The authors proposed introducing regulations that would directly indicate how to appoint a tax collector. The research method used in the study is the dogmatic-legal method and the analysis of local government resolutions, resolutions of the boards of the Regional Chambers of Audit and judgments of administrative courts.